2022
DOI: 10.1155/2022/3661866
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds and Therapeutics from Fish: Revisiting Their Suitability in Functional Foods to Enhance Human Wellbeing

Abstract: Global public awareness about fish-based diet and its health/nutritional benefits is on the rise. Fish nutritional profile projects promising bioactive and other compounds with innumerable health benefits for human wellbeing. As various reported researches involving fish/marine-derived molecules reveal promising attributes, and as the position of fish-based nutrients as nutraceuticals continue to strengthen, health challenges still confront communities worldwide, from cardiovascular disease, diabetes, and obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 145 publications
(232 reference statements)
1
27
0
Order By: Relevance
“…Therefore, egg proteins are very effective against atopic disease, edematous malnutrition, inflammation, and weight loss in infants (Guha et al, 2019;Mine, 2015;Strixner & Kulozik, 2011). cially IgA, has the potential to provide the first line of defense against pathogenic microbes, including viruses and bacteria (Awuchi, Akram, et al, 2022;Awuchi, Chukwu, et al, 2022;Woof & Kerr, 2006). The findings of current research work are similar to the study in which celiac disease patients were treated with egg protein powders for a period of 6 months.…”
Section: Serum Proteinssupporting
confidence: 62%
See 1 more Smart Citation
“…Therefore, egg proteins are very effective against atopic disease, edematous malnutrition, inflammation, and weight loss in infants (Guha et al, 2019;Mine, 2015;Strixner & Kulozik, 2011). cially IgA, has the potential to provide the first line of defense against pathogenic microbes, including viruses and bacteria (Awuchi, Akram, et al, 2022;Awuchi, Chukwu, et al, 2022;Woof & Kerr, 2006). The findings of current research work are similar to the study in which celiac disease patients were treated with egg protein powders for a period of 6 months.…”
Section: Serum Proteinssupporting
confidence: 62%
“…Moreover, the immunoglobulin E (IgE) level remained unchanged in all pups fed high levels of egg protein and plant protein diets. The type of immunoglobulin, especially IgA, has the potential to provide the first line of defense against pathogenic microbes, including viruses and bacteria (Awuchi, Akram, et al, 2022 ; Awuchi, Chukwu, et al, 2022 ; Woof & Kerr, 2006 ). The findings of current research work are similar to the study in which celiac disease patients were treated with egg protein powders for a period of 6 months.…”
Section: Resultsmentioning
confidence: 99%
“…[ 28 ] It is well‐established that salmon, spiny dogfish, mackerel, anchovies, and sardines are excellent sources of ω‐3 and ω‐6. [ 29 ] The ω‐3 PUFA's have been linked to reduce cholesterol levels and prevention of cardiovascular, neurological, and inflammatory diseases. [ 25 ] Due to their higher lipid content, some fish, such as mackerel, anchovies, salmon, herring, sardines, sprats, and farmed trout, have a higher concentration of ω‐3 PUFA's (1.4–2.5 g of EPA and DHA per 100 g muscle tissue).…”
Section: The Nutritional Composition Varies Markedly In Fishmentioning
confidence: 99%
“…[ 45 ] In addition, fish oil's ω‐3 fatty acid (DHA), present in fatty fish such as salmon, tuna, herring, trout, sardines, and yellowfin, reduce depression and improve cognition and intellectual deterioration. [ 29 ] A recent meta‐analysis [ 46 ] concluded that fish intake of 250 g week −1 was associated with a 10% reduction in all‐cause dementia and a 30% reduction in Alzheimer's disease risk. The absence of beneficial effects from consuming fish in more significant quantities or even the predominant consumption of only certain species may be explained by the presence of local contaminants, such as methylmercury.…”
Section: General Health Benefits Of Regular Fish Consumptionmentioning
confidence: 99%
“…Because of these qualities, RS has been effectively included into a wide range of foods, including baked goods, pasta, and dairy products, [29,30]. RS has also been used to microencapsulate probiotics in dairy products [31] in an endeavour to boost viability, as well as fish oil to minimize oxidation as well as odour [32].…”
Section: Resistant Starch As a Functional Foodmentioning
confidence: 99%